Find A Correction Factor Between The Analytical And Numerical Solution For Reynolds Equation (With And Without) Considering THL Effect (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper ,an analytical study of a conventional hydrodynamics bearing was carried out. Anintegrated program was built using a computer program and through the Matlab facility in orderto solve Reynolds equation numerically using finite difference method and analytically throughthe short bearing theory.The effects of the thermal distortion on the bearing performancearestudied. The thermal distortion is a result of the temperature riseeffects. This study wascarried out for journal speed 3000 rpm. The oil film pressure distribution is obtained by solvingReynolds equationnumerically and analytically.Pinkus's approach has been used in computingthe temperature distribution along the circumferential direction of the bearing surface. Analyticalsolution for Reynolds equation overestimates the bearing characteristics and Capacity comparedwith numerical solution results. It was found that THL effect the bearing performance positively(in the low range of temperature) by increasing stiffness and load capacity also it was found thatusing correction factor is useful to get more accurate assessment for the bearing performance bysolving Reynolds equation analytically.